2014
DOI: 10.5901/jesr.2014.v4n1p231
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Interactional Metadiscourse Markers and Gender in the Defense Seminars of Persian Speakers

Abstract: This paper aims to analyze the relation between a linguistic behavior, namely interactional metasdicourse, and a non-linguistic variable, namely, gender in thesis defenses of Persian speakers. Based on the model of community of practice, a qualitative and quantitative analysis of the metadiscourse markers employed by male and female candidates in thesis defenses have been carried out. The data include eighteen thesis defenses of nine males and nine females in humanities and social sciences. The quantitative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Thus, (Hyland, 2005) distinguishes the model of metadiscourse into two categories, they are interactive and interactional metadiscourse. The interactive metadiscourse centers on the content of the text, while the interactional focus on the participants of the interaction (Zareifard & Alinezhad, 2014). Both interactive and interactional resources being as two interrelated modes of interaction (Thompson, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, (Hyland, 2005) distinguishes the model of metadiscourse into two categories, they are interactive and interactional metadiscourse. The interactive metadiscourse centers on the content of the text, while the interactional focus on the participants of the interaction (Zareifard & Alinezhad, 2014). Both interactive and interactional resources being as two interrelated modes of interaction (Thompson, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Hyland (2005) also explained that "these markers are realized in deontic verbs (should, have to), attitudinal adverbs, adjectival constructions, and cognitive/mental verbs which instead of commenting on the status of information, its probable relevance, reliability or truth, attitude markers convey surprise, agreement, importance, obligation, frustration, and so on." Example: Unfortunately, the level of health is very low among agers in Iran (Zareifard & Alinezhad, 2014).…”
Section: Attitude Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a considerable amount of studies which analyze the particular features of metadiscourse markers (Abdi, 2009;Bunton, 1999;Hyland & Tse, 2004;Ifantidou, 2005;Adel, 2010;Kondowe, 2014). Many researchers have focused on the use of metadiscourse markers from cross-cultural (Blagojevic, 2004;Burneikaite, 2008;Mur-Duenas;2011;Özdemir & Longo, 2014;Çapar, 2014), cross-disciplinary (Dahl, 2004;Hyland, 1998;Hyland, 1999;Hyland, 2004;Hyland, 2010;Rezaei et al, 2015;Salas, 2015) and gender-based perspectives (Yavari & Kashani, 2013;Yeganeh, 2014;Zareifard & Alinezhad, 2014;Zadeh et al, 2015;Salehi & Biria, 2016). Despite widespread interest and research among applied linguists to explore metadiscourse use, Keramati and colleagues (2019) called upon "very little is known of how metadiscourse resources have evolved over time in response to the historically developing practices of academic communities".…”
Section: Extended Summarymentioning
confidence: 99%
“…The body of research studies on written texts examined in recent years covers text types like textbooks [12], studentproduced texts [13], research abstracts [14], research articles [15], and newspapers editorials [16]. In contrast, the prevailing body of studies found in spoken texts are political speeches [17], thesis defense [18], speaking ability of English language learners [19], academic lectures [20], and other generally inspiring speeches [21]. These studies on spoken texts revealed that metadiscourse is clearly not a feature that speakers can dispense with when they deliver speeches.…”
Section: Introductionmentioning
confidence: 99%